2013
DOI: 10.1128/jcm.02480-12
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal Outbreak of KPC-3-Producing Enterobacter cloacae at a Single Hospital in Montréal, Québec, Canada

Abstract: , 26 KPC-3-producing Enterobacter cloacae isolates were identified from 16 patients at a single hospital. Analyses revealed the bla KPC gene to be localized on multiple plasmids in a diverse nonclonal E. cloacae genetic background. These findings highlight the potential complexity of a KPC outbreak at a single hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 8 publications
2
17
1
Order By: Relevance
“…have been described in North America, 18 but no plasmid-borne carbapenemases (or cephalosporinases) were detected in the Enterobacter isolates in this study. The positive MHT results in these isolates suggest the production of beta-lactam-hydrolyzing enzymes, such as de-repressed chromosomal AmpC determinants or constitutively expressed plasmid-borne enzymes that were not captured by our panel.…”
Section: Discussioncontrasting
confidence: 67%
“…have been described in North America, 18 but no plasmid-borne carbapenemases (or cephalosporinases) were detected in the Enterobacter isolates in this study. The positive MHT results in these isolates suggest the production of beta-lactam-hydrolyzing enzymes, such as de-repressed chromosomal AmpC determinants or constitutively expressed plasmid-borne enzymes that were not captured by our panel.…”
Section: Discussioncontrasting
confidence: 67%
“…This work demonstrated that plasmid transfer between unrelated strains and species of bacteria within a hospital might be further contributing to the dissemination of CP-CRE (3). Other reports of the apparent in vivo transfer of plasmids exist (19), with evidence of plasmid-mediated transfer of bla between E. cloacae isolates in a health care setting (20).…”
supporting
confidence: 50%
“…Since its initial identification, sporadic cases with KPC-harboring Enterobacter spp. have been described and several outbreaks have been reported worldwide (1015). According to two surveillance studies (in 2006 and 2009), a total of 758 KPC-positive Gram-negative isolates were collected, revealing that Enterobacter spp.…”
Section: Introductionmentioning
confidence: 99%